bell hooks e Educação Infantil: por uma pedagogia feminista, antirracista e amorosa - Nazario, Beatriz da Silva (Universidade Federal de São Carlos, 2025)
This thesis analyzes bell hooks' contribution to the field of early childhood education, with special attention to her conception of gender, her critique of structural inequalities, and the transformative potential of her children's books. Based on the intersectional perspective developed by the author, which articulates race, gender, class, and criticism of capitalism, we seek to understand how hooks offers theoretical, political, and pedagogical foundations for thinking about feminist and anti-racist education from early childhood. The literature review seeks to understand the concept of gender and the relationship between gender inequality and education, the history of childhood and early childhood education in Brazil, situating the child as a social, political, and cultural individual. Then, we discuss the centrality of childhood in hooks' work, highlighting how her writing, marked by the ethics of love, provides an engaged pedagogy focused on freedom. It is expected that the reflections will contribute to expanding the debate on the need of a feminist, anti-racist, and loving pedagogy in early childhood education.
bell hooks and Early Childhood Education: for a feminist, anti-racist, and loving pedagogy
Keywords: bell hooks; Educação infantil; Desigualdade de gênero; Pedagogia feminista; Childhood education; Gender inequality; Feminist pedagogy; CIENCIAS HUMANAS::EDUCACAO; 5. Igualdade de Gênero; 10. Redução das Desigualdades